Králíčková, Z., Žatecká, E., Dávid, R., Kornel, M.: Právo proti domácímu násilí - Monika Schön (Časopis pro Právní Vědu a Praxi, 2012)
Recenze publikace - Králíčková, Z., Žatecká, E., Dávid, R., Kornel, M.: Právo proti domácímu násilí